Beyond comfort: unmasking the synergy between human needs and environmental behaviour - Abu Bakar, Aisyah (Malaysian Institute Of Planners, 2024)
This research empirically investigated the relationship between environmental behaviour [EB] and meeting human needs based on Maslow's Hierarchy of Needs [HON] within the realm of Subjective Well-Being [SWB] and Human Interdependence [HI]. Research Questions: Does EB increase when human needs are conveniently satisfied? Can EB increase even if human needs are unmet, and if so, which human needs have little effect on EB? Purpose: This paper determines the variance of EB across the convenience and difficulty of meeting human needs. Approach: Mann-Whitney U test was conducted to determine the variance of EB across the convenience and difficulty of meeting 24 human needs. Findings: EB significantly increased with the convenience of meeting 13 human needs. Neither convenience nor difficulty of addressing the other 11 human needs affect EB, indicating their unlikeliness to have an impact on EB. Furthermore, EB can evolve independently of meeting human needs.